MARKETING STRATEGY OF “QURO HEXAGONAL DRINKING WATER” PRODUCTS IN KOPERASI PESANTREN AL-QUR’AN, CIJANTUNG-CIAMIS - Sumarni Sumarni; Deni Yusuf Hidayat; Muhamad Purnama Dipraja (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2021)
Water is an essential need for living things, especially water for consumption. In Indonesia, the demand for clean water is constantly increasing, thus providing an opportunity to open a business in the field of Bottled Drinking Water (AMDK). Pondok Pesantren Al-Qur’an Cijantung Ciamis has a drinking water company business unit “Quro Hexagonal” long been marketed in various regions. This study aims to determine the marketing strategy, product, price, distribution, place and promotion used in the Quro Hexagonal water company. This study uses a qualitative field method. Test the validity of the data using triangulation. The results showed that to meet consumer demand, company management uses four marketing strategies, namely product, price, distribution, and promotion. This Quro Hexagonal water product uses a Life Energy engine, a mineral water system, from this process it will produce quality water. The prices that the company offers are high prices because of the excellent water quality. Distribution, Quro Hexagonal water company in running its business to market its products has reached the cities of Banjar, Pangandaran, Tasikmalaya, Kuningan, Majalengka, Cirebon, and surrounding areas. Promotion, the Quro Hexagonal water company conducts sales promotions by utilizing the distribution of the alumni of the Cijantung Al-Qur’an Islamic Boarding School to become agents or consumers of Quro Hexagonal water.